Usages Socioeconomiques Des Espèces Ligneuses Au Sahel: Cas De Guidan Roumdji Au Niger - Ousmane, Laminou M.; Morou, Boubé; Karim, Saley; Garba, Oumarou Bachir; Mahamane, Ali (European Scientific Journal, ESJ, 2017)
Woody species are of multiple use in the department of Guidan- Roumdji, in Niger. The present study carried out in Garin-yahaya and Tsayin-daka aims to identify the woody species, their different uses and to determine their present state. Data collection methodology consisted of a floristic inventory at the level of 80 plots and ethnobotanical surveys on a sample of 250 respondents. 46 species, divided into 38 genera and 22 families, were recorded. There were 24 species used in food, 19 fodder species and 38 others species used in the treatment of several ailments in the area. Also, in handicrafts and construction, a dozen species are used respectively against 19 others species in the production of wood energy. These diverse and wide-ranging uses, associated with the effects of climate change, affect the woody species populations. Thus, in the area, 25 species are declared extinct, 18 and 14 others are respectively considered threatened and rare. The study also reported on woody species management practices in the area, including the conservation of 7 local species and the introduction of 11 exotic species because of various products and services they provide. Also, 96% of the local population practices the trees’ farming natural regeneration management (FNRM) in their farms for various reasons. This would be a start in the sustainable and rational management of forest resources in the area with the maintenance of several woody species in the area.